REPRESENTASI MENTAL SISWA SMA DALAM MEMBACA GAMBAR BIOLOGI - Adi Rahmat; Soesy Asiah Soesilowaty; Eni Nuraeni; Yogi Yogi; Imam Nugroho; Meilia Gemilawati (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2017)
In learning biology, teachers often use visual media, such as diagrams, to help students understand the concept. This study was focused on how students’ mental representation (MR) when they read biological diagrams, either representation convention diagram or spatial isomorphism diagram. The student’s MR was analyzed using a worksheet modified from an MR measurement model of CNET protocol. This model involves three main components of the MR’s working memory: causal network, probability parameter, and utility parameter. Ninety 11th grade students of a senior high school in Bandung voluntarily involved in this study. Only 59 students, however, performed the worksheet completely. The result revealed that each student gave a different pattern of MR either when he/she read convention or spatial diagram. These differences could be traced since the student decides and orders the information elements and makes a causal network. Based on this result, we suggest that this method of MR analysis using a worksheet can be used to understand how student’s working memory works on MR building when they read a diagram. Understanding how the student can construct MR is a necessary platform to provide appropriate visual media that will help the student improve their learning achievement.